Strikes, Scabs and Tread Separations: Labor Strife and the Production of Defective Bridgestone/Firestone Tires - Alan B. Krueger; Alexandre Mas (Institute for the Study of Labor (IZA), 2003)
This paper provides a case study of the effect of labor relations on product quality. We consider whether a long, contentious strike and the hiring of replacement workers at Bridgestone/Firestone?s Decatur plant in the mid-1990s contributed to the production of defective tires. Using several independent data sources, and looking before and after the strike and across plants, we find that labor strife at the Decatur plant closely coincided with lower product quality. Monthly data suggest that defects were particularly high around the time concessions were demanded and when large numbers of replacement workers and returning strikers worked side by side.
Keywords: M5; J5; M1; 330; labor relations; product quality; Bridgestone/Firestone; strike; Arbeitsbeziehungen; Produktqualität; Arbeitsbedingungen; Arbeitszufriedenheit; Theorie; Reifenindustrie; Vereinigte Staaten